2011
DOI: 10.1148/radiol.11103503
|View full text |Cite
|
Sign up to set email alerts
|

Improved Perfusion MR Imaging Assessment of Intracerebral Tumor Blood Volume and Antiangiogenic Therapy Efficacy in a Rat Model with Ferumoxytol

Abstract: Purpose:To evaluate the consistency of tumor blood volume measurements and antiangiogenic therapy effi cacy assessments with a low-molecular-weight gadolinium-based contrast agent (GBCA, gadodiamide) versus an iron oxide nanoparticle (ferumoxytol) in the presence or absence of a loading dose of contrast agent before perfusion magnetic resonance (MR) imaging (preload method). Materials and Methods:The protocol was approved by the institutional animal care and use committee. U87MG tumor cells were implanted intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…Leakage correction works best with limited extravasation rates, above which the blood space and extravascular extracellular space becomes intrinsically indistinguishable when GBCA is used, and the derived rCBV value and leakage rate are no longer independent. The results of our preclinical rodent study also showed that brain tumor rCBV was underestimated when GBCA was used in a human high-grade glioma xenograft, and the accuracy of the measurement was improved by using the preload leakage correction method; however, rCBV values depended on the dose of contrast agent preload (37). By using ferumoxytol for DSC MR imaging in the same animals, we obtained consistent and rCBV underestimation, which can potentially lead to incorrect diagnosis, treatment, and prognosis and necessity of leakage correction.…”
Section: Neuroradiology: Pseudoprogression Of Glioblastoma After Chemmentioning
confidence: 67%
See 1 more Smart Citation
“…Leakage correction works best with limited extravasation rates, above which the blood space and extravascular extracellular space becomes intrinsically indistinguishable when GBCA is used, and the derived rCBV value and leakage rate are no longer independent. The results of our preclinical rodent study also showed that brain tumor rCBV was underestimated when GBCA was used in a human high-grade glioma xenograft, and the accuracy of the measurement was improved by using the preload leakage correction method; however, rCBV values depended on the dose of contrast agent preload (37). By using ferumoxytol for DSC MR imaging in the same animals, we obtained consistent and rCBV underestimation, which can potentially lead to incorrect diagnosis, treatment, and prognosis and necessity of leakage correction.…”
Section: Neuroradiology: Pseudoprogression Of Glioblastoma After Chemmentioning
confidence: 67%
“…Paulson et al (35) found variability in tumor rCBV depending on the choice of five different mathematic correction algorithms. Moreover, our preclinical study (37) results showed the inconsistency of preload methods for leakage correction. The most commonly used of these two methods required either sophisticated postprocessing or high contrast-agent dose exposure but was still inconsistent.…”
Section: Neuroradiology: Pseudoprogression Of Glioblastoma After Chemmentioning
confidence: 91%
“…Based on our prior work, immediate post-USPIO MRI shows intravascular, not abnormal parenchymal enhancement. [22][23][24] The second day of imaging at 24 hours is a relatively intracellular-weighted (and/or interstitial-weighted) rather than intravascular-weighted MRI given that ferumoxytol has an intravascular halflife of approximately 14 to 20 hours. 25 This proved helpful in one patient in this series who underwent a second diagnostic biopsy in which a different surgical target was selected based on the T2-weighted USPIOenhanced MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Can characterize tissues and pathologic processes at the microscopic level ADC depends on sampling method -confounded by necrosis, vascularity MR perfusion [38,43,[53][54][55][56][57][58][59][60][61][62] Higher rCBV in areas of enhancement Studies have correlated rCBV values to tissueconfirmed diagnoses [53] and survival [59] Vascular leak problematic, requires correction; rCBV value cutoffs vary by technique, institution…”
Section: Strengths Limitationsmentioning
confidence: 99%